O Ministério Público e o termo de ajustamento de conduta - Bastos Filho, Orlando (2008)
The work analyzes non jurisdictional alternatives for the resolution of conflicts of interests involving metaindividual rights, especially when tutored by the public prosecution service. The elect procedural instrument is the term of adjustment of conduct, as ruled by the Laws ns. 7.347/85 and 8.078/90. The research begins with the verification of the procedural congestion that desolates the Judiciary; it continues with considerations on the origins of the public prosecution service, its evolution, besides in the Brazilian State, under the light of all the Constitutions that were valid in the territory, standing out the profile traced by the one now effective; and it finishes with the evaluation of the term of adjustment of conduct, its antecedents, legal positioning, object, nature, legitimated, formalization, validity and modifications. The importance of the transindividual interests, especially by their extension and width, associated to the incapacity of the Judiciary in offering swift answers for the proceedings involving them, brings the need of use of non judicial expedients, in the case the term of adjustment of conduct, with distinctive valour, by the public prosecution service, outstanding actor in the guardianship of the collectivity s interests